Evaluation of Software Tell Me More for Teaching English : Technology Acceptance Model Approach - Septika Ariyanti; Defy Gustianing; M. Fatkhu Arifin (UIR Press, 2021)
Knowing the students’ technology acceptance about the use of learning media is important because it can measure how far the media’s utilisation is.The research purpose is to recognize the significant influence between the variable of Technology Acceptance Model, such as perceived usefulness, perceived ease of use, attitude towards use and behaviour intention in accepting software Tell Me More for teaching English. The participants of this research consisted of 51 students of English Education Study Program from Universitas Muhammadiyah Metro. Questionnaire was used to find out the students’ acceptance towards the use of software Tell Me More. Regression analysis is applied to analyze the data. Based on the data analysis through the questionnaire, it is revealed that there was significant influence between the variable of technology acceptance model towards the students’ acceptance of Tell Me More software.